The creolizing subject : race, reason, and the politics of purity - Monahan, Michael J. (Just ideas., 2011)
Drawing upon a close engagement with historical treatments of the development of racial categories & identities, the book argues that races should be understood not as clear & distinct categories of being but rather as ambiguous & indeterminate (yet importantly real) processes of social negotiation.